Comparative life cycle assessment of traditional and sustainable building materials for residential construction - Muhammad Adam Mohamad Fauzilah (2024)
In this study, the life cycle assessment method was used to assess the impact of traditional and sustainable building materials on the environment. This life cycle assessment consists of 4 phases based on ISO14044 and ISO 14040. The phases are the goal and scope definition phase, the inventory analysis phase, the impact assessment phase and the interpretation phase. In the inventory analysis phase, traditional and sustainable building materials are selected for analysis. Subsequently, this selection underwent further scrutiny using the openLCA software, which facilitated the generation of conclusive results for this life cycle assessment. This software produces the final results for this life cycle assessment. Using rigorous methodology and advanced tools, this study aims to provide valuable insights into the environmental implications of adopting traditional versus conventional building materials, thereby aiding the practical decision-making process.